Shifting gender regimes: The complexities of domestic violence among Canada's Inuit - Billson, Janet (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2006)
AbstractThis article brings the voices of Inuit women into the discourse on domestic violence as a core issue in their communities. The views of Inuit women interviewed as part of a case study of Pangnirtung, Nunavut Territory between 1988 and 2002 are accompanied by statistics on patterns of domestic violence. The Canadian Government brought the Inuit from the land to this small Baffin Island hamlet during the 1960s. The sources of domestic violence are framed within the context of female well-being and the impacts of resettlement, rapid social change, and women’s rights as human rights. Traditional patterns of domestic violence, as reported by Inuit women, are compared to contemporary rates. Inuit women across generations explore the precipitating factors and impacts of domestic violence. Insofar as domestic violence results from shifting (and unbalanced) gender regimes, in this case amplified by rapid social change, it may be a transitional phenomenon. As the Inuit develop new cultural forms, and political and economic stability emerge from the creation of Nunavut, domestic violence rates should decline. Because individual well-being contributes to general social well-being and vice versa, women and their communities are likely to experience a lower level of both objective and subjective well-being until domestic violence has been reduced.